Kerajaan Mughal di India: Telaah Historis Kebijakan Kekuasaan dalam Perspektif Kaidah Fiqh Siyasah - Putri Humaira Djufri; Ansar Tohe (Al-Kindi, 2026)
The Mughal Empire was one of the three great Islamic gunpowder empires that ruled the Indian subcontinent for more than three centuries, from 1526 to 1858 CE. This article examines the origins, development, golden age, and decline of the Mughal Empire, analyzing them through two principles of fiqh siyasah and ushul fiqh: tasharruf al-imam ‘ala ar-ra’iyyah manutun bi al-maslahah (a ruler’s policy toward the people must always be oriented toward the common good) and dar’u al-mafasid muqaddamun ‘ala jalb al-masalih (preventing harm takes precedence over pursuing benefit). This study employs a qualitative method with a historical-normative approach through library research. The findings show that the golden age under Akbar the Great was closely linked to maslahah-oriented policies such as the abolition of jizyah, the mansabdari system, and interfaith tolerance, consistent with the principle of tasharruf al-imam. Conversely, the decline under Aurangzeb reflects a departure from the principle of dar’u al-mafasid, as policies of religious intolerance generated greater socio-political harm in the form of widespread resistance and political disintegration. This study affirms the relevance of fiqh siyasah principles as a normative framework for reading the dynamics of Islamic political power throughout history, offering lessons for contemporary Muslim leadership.